2000
DOI: 10.1200/jco.2000.18.11.2226
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Amifostine During Fractionated Radiotherapy: A Randomized Phase II Study

Abstract: Subcutaneous administration of amifostine is well tolerated, effectively reduces radiotherapy's early toxicity, and prevents delays in radiotherapy. The subcutaneous route is much simpler and saves time compared with the intravenous route of administration and can be safely and effectively applied in the daily, busy radiotherapy practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
131
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(137 citation statements)
references
References 21 publications
3
131
2
1
Order By: Relevance
“…Studies evaluating the prophylactic use of amifostine during radiotherapy have uniformly reported a reduction of the incidence and severity of oral mucositis, but produced inconsistent results concerning the tolerability of the substanceregardless of its dosage and route of administration. [180][181][182] Similarly, three out of four studies have demonstrated mucosaprotective effects of amifostine during simultaneous radiochemotherapy. [183][184][185][186] Data on the use of amifostine in the prevention of chemotherapy-induced oral mucositis are scant, because the evaluation of mucositis does not constitute a primary endpoint of most studies.…”
Section: Amifostinementioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the prophylactic use of amifostine during radiotherapy have uniformly reported a reduction of the incidence and severity of oral mucositis, but produced inconsistent results concerning the tolerability of the substanceregardless of its dosage and route of administration. [180][181][182] Similarly, three out of four studies have demonstrated mucosaprotective effects of amifostine during simultaneous radiochemotherapy. [183][184][185][186] Data on the use of amifostine in the prevention of chemotherapy-induced oral mucositis are scant, because the evaluation of mucositis does not constitute a primary endpoint of most studies.…”
Section: Amifostinementioning
confidence: 99%
“…A series of clinical trials have reported on mucosaprotective effects of subcutaneous dosages up to 500 mg and on intravenous use at doses up to 740 mg/m 2 . [180][181][182][183][184][185][186][187][188][189] Side effects, mostly nausea and hypotension, seem to be more pronounced at higher doses and upon intravenous use, whereas, the optimal mucosaprotectant dose and route of administration remains to be defined. Studies evaluating the prophylactic use of amifostine during radiotherapy have uniformly reported a reduction of the incidence and severity of oral mucositis, but produced inconsistent results concerning the tolerability of the substanceregardless of its dosage and route of administration.…”
Section: Amifostinementioning
confidence: 99%
“…During the days of radiotherapy (Tuesday to Friday), amifostine was given subcutaneously, as previously described (Koukourakis et al, 2000a). Patients were pretreated with 5 mg of oral Tropisetron (Navoban Ò , Novartis) 1 -2 h before the subcutaneous injection of amifostine.…”
Section: Administration Of Amifostinementioning
confidence: 99%
“…In the present dose escalating study we show that standard radiotherapy can be safely combined with high doses of two drugs, namely Stealth Ò liposomal doxorubicin (Caelyx Ò ) and Docetaxel (Taxotere Ò ), if subcutaneous amifostine is used as a broad spectrum cytoprotective agent (Koukourakis et al, 2000a).…”
mentioning
confidence: 99%
“…Although WR-2721 (amifostine) is the only radioprotector that has been approved by the US Food and Drug Administration at present, it has some severe adverse effects including nausea, vomiting, lethargy, and hypotension with large toxicity (Landauer et al, 1987;Koukourakis et al, 2000). Furthermore, amifostine must be administrated by the intravenous route, which restricts its clinical usage in patients.…”
Section: Introductionmentioning
confidence: 99%